Optical properties of As2S3-based suspended-core photonic crystal fiber - Hoang, Duc Trong; Tran, Nam Hai; Nguyen, Thi Thuy (Hue University Journal of Science: Natural Science, 2022)
In this paper, the nonlinear properties of photonic crystal fibers (PCF) with As2S3 substrate were analyzed numerically. With the suspended-core design, we achieve an anomalous dispersion regime with one or two zero-dispersion wavelengths, which is flat and has a small value at the investigated wavelength. The high nonlinear coefficient and very low confinement loss in the wavelength range of 1–3 µm, in comparison with other publications, are the outstanding advantages of these suspended-core PCFs. The highest nonlinear coefficient (28,527.374 W–1·km–1), smallest effective mode area (0.593 µm2), and low confinement loss (6.050 × 10–17 dB·m–1) at the wavelength of 1.55 µm were observed in the PCFs with a fiber diameter of 16.07 μm. Based on the numerical simulation results, we proposed two optimal structures suitable for supercontinuum generation.